Corporate Board Attributes, Shariah Board Attributes and Credit Rating: Evidence from Islamic Banks of Pakistan - Muhammad Mansoor; Nazima Ellahi; Qaiser Ali Malik (Türkiye İslam İktisadı Dergisi)
Shariah Governance is an essential characteristic that differentiates Islamic financial institutions from Conventional financial institutions. The study’s purpose is to explore the effect of corporate governance attributes and Shariah board attributes on the long term and short-term credit rating of Islamic banks in Pakistan. The study develops six different models based on corporate board characteristics, Shariah board attributes and credit ratings, and collected data from annual reports of Pakistani Islamic banks for the period 2013- 2019. This study used Long term credit rating scale used by Grassa (2016) and, Ashbaugh-Skaife, Collins, and LaFond (2006), and developed a Short term credit rating scale. The study applied descriptive statistics, correlations and ordered logit regression. The results confirmed that corporate governance and Shariah governance attributes are significantly associated with the long term and short-term credit ratings of Islamic banks. The study concludes that credit rating agencies in Pakistan i.e. PACRA and JC-VIS, and other international credit rating agencies including Fitch, Moody and Standard & Poor’s must consider Shariah governance attributes as key determinants while assigning long term and short term credit ratings to Islamic banks.